The Fehmarn Belt duopoly: Can the ferry compete with a tunnel? - Rafael Aigner (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
The Fehmarn Belt is a strait between Denmark and Germany, currently served by a ferry. This note analyses the theory of competition between the ferry and a planned tunnel, the Fehmarn Belt Fixed Link. The model is an asymmetric duopoly and addresses two questions: 1. Will the tunnel induce the ferry to exit the market, once it operates? 2. Will the tunnel's toll revenue suffice to cover its cost? To complement the theoretical analysis, the note provides results of a numerical application.
Keywords: R42; D43; L91; 330; Fehmarn Belt Fixed Link; transportation economics; competition analysis; route choice; asymmetric duopoly